1993
DOI: 10.2307/1939308
|View full text |Cite
|
Sign up to set email alerts
|

Moose Browsing and Soil Fertility in the Boreal Forests of Isle Royale National Park

Abstract: Selective foraging by moose on hardwoods and avoidance of conifers alters community composition and structure, which in turn can affect nutrient cycles and productivity. The effect of moose browsing on the nutrient cycles of boreal forests was studied using three 40—yr—old exclosures on Isle Royale, Michigan. Two alternative mechanisms by which moose affect ecosystems were tested: (1) moose depress both the quantity and quality of litter return to the soil, and hence N mineralization and net primary productivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
450
7
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 447 publications
(475 citation statements)
references
References 32 publications
(40 reference statements)
16
450
7
2
Order By: Relevance
“…This is not surprising as the effects of herbivory on forage quality and nutrient cycling (Pastor et al 1993;de Mazancourt et al 1998;Sirotnak & Huntly 2000) differ at different temporal scales. However, short-term grazing enhancement proved to be an effective indicator of long-term effects, although the same was not true of short-term grazing reduction.…”
Section: Discussionmentioning
confidence: 99%
“…This is not surprising as the effects of herbivory on forage quality and nutrient cycling (Pastor et al 1993;de Mazancourt et al 1998;Sirotnak & Huntly 2000) differ at different temporal scales. However, short-term grazing enhancement proved to be an effective indicator of long-term effects, although the same was not true of short-term grazing reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have documented the stimulation of nitrogen cycling by herbivores (e.g., Ruess andMcNaughton 1987, Frank andGroffman 1998), and some have reported a deceleration of nitrogen cycling as an indirect consequence of selective herbivory (Pastor et al 1993, Ritchie et al 1998), but no studies have examined both mechanisms simultaneously in a site. We found that the net effect of vole herbivory on soil organic matter quality differed between two study sites.…”
Section: Discussionmentioning
confidence: 99%
“…Selective foraging on high-quality plants, e.g., plants with a relatively low C:N ratio or with low concentrations of recalcitrant chemicals, can decrease the abundance of these plants relative to plants of lower quality (McInnes et al 1992, Ritchie et al 1998). The relatively low-quality plant litter mineralizes nitrogen at a slower rate than would occur in the absence of herbivory (Pastor et al 1988(Pastor et al , 1993. The objective of this study was to determine the effects of voles (Microtus, Rodentia: Microtinae) on nitrogen dynamics in riparian meadows in Yellowstone Park.…”
Section: Introductionmentioning
confidence: 99%
“…By consuming plant material, herbivores influence decomposition and nutrient cycling in communities (Pitelka 1964;Schultz 1964;Kitchell et al 1979;Swank et al 1981; Pastor and Cohen 1997). Experimental studies havc confirmed the role of vertchrate herbivores as mcdiators of decomposition processes in terrestrial systems iMc1n11cs et al 1992; Molvar et al 1993;Pastor et al 1993;Ritchic ct al. 1998).…”
Section: Herbivores As Mediators Of Forest Processesmentioning
confidence: 99%